Three Dimensional Simulation of Changes in Air Flow on a Jet Engine Desktop Based - Retnowati, Nurcahyani Dewi; Mulyani, Sri; Talantha, Frencha (Compiler, 2019)
Learning about changes in air flow on jet engines requires a clear understanding because there are parts of the jet engine that work according to their functions and are interconnected. People often have difficulty understanding learning about changes in air flow in the jet engine and also about the brayton cycle. This study aims to make a simulation that explains the changes in air flow in a jet engine with a three-dimensional animated form in order to improve understanding of learning about it. The process of making three-dimensional simulations uses animation modeling techniques, texturing, lighting, editing, and rendering. In modeling and texturing on jet engines following the Brayton cycle. The three-dimensional simulation results show that this simulation can be run by computers with Windows 7 and Windows 8 operating systems, and from the results of user test analysis 80.2% agree that this three-dimensional simulation can be understood and can explain changes in airflow in jet engines.